Fostering Investment-Innovative Activity within the Agro-Industrial Complex of the Republic of Kazakhstan - MADIYEV, Galizhan; KERIMOVA, Ukilyay; YESPOLOV, Aidos; BEKBOSSYNOVA, Assel; RAKHIMZHANOVA, Gaukhar (Journal of Environmental Management and Tourism; Vol 9 No 3 (2018): JEMT Volume IX Issue 3(27) Summer 2018, 2018)
A crucial attribute of today’s agrarian sector is the dynamicity of economic processes, which is reflected in the rapid pace of scientific-technical process and stiffening competition. These processes are characterized by varying scales and types of activity by agricultural enterprises, the complexification of economic relationships between them, changes in demand and prices for products, a growing need for fixed and current assets, the emergence of new markets, and the liberalization of state regulation. The purpose of this paper is to provide a rationale for economic mechanisms for galvanizing investment-innovative processes within the agro-industrial complex of the Republic of Kazakhstan, the practical implementation whereof is governed by the actions of market entities within it. The possible ways to resolve this issue are examined through the lens of relevant measures for attaining economic growth, which is governed by the factors of demand and supply and the degree to which the nation utilizes its resource potential and the achievements of technical progress, an increased scale of production, and boosts in the efficiency of mechanisms for state regulation of the development of the nation’s agro-industrial complex. The authors have conducted an assessment of the current state of the development of Kazakhstan’s agro-industrial complex, as the subject of this study, and based on the findings put forward a set of economic organizational measures for the development of investment-innovative activity. These measures focus on remediating disparity in prices for agricultural and industrial output, regulating activity within agrarian markets, managing investment activity, and enhancing the instruments of government regulation stimulating the galvanization of investment-innovative processes and attraction of foreign investors into the nation’s agricultural machine-building sector.